1968
DOI: 10.1063/1.1670162
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Acceleration of the Electrodic Dissolution of Metals during Yielding under Stress

Abstract: The effect of strain, in particular the effect of varying the rate of its application, both in the elastic and the plastic region, on the anodic dissolution kinetics of several metals has been studied. It has been found in the case of iron in acid solution that the over-all effect of elastic strain is small (i.e., the shift of corrosion potential is about +0.1 mV/1000 kg cm−2) and is mostly due to the change in the rate of hydrogen evolution. The effect of yielding on the rate of the electrodic dissolution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0
4

Year Published

1974
1974
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(42 citation statements)
references
References 33 publications
1
37
0
4
Order By: Relevance
“…Under external load, it has been generally agreed that the plastic strain will significantly reduce the corrosion resistance by directly enhancing the anodic reaction [7,11,14,16,[21][22][23][24][25][26] while the hydrogen evolution was reported to increase as well [21,22]. Despic et al [11] observed that a negative corrosion potential shifted by up to 30 times, with a marked increase in the anodic current density at the onset of the tensile plastic strain and reached an asymptotic value gradually. Plastic deformation was believed to increase the surface reactivity non-uniformly [26] and the stored energy within a material, which can be directly related to the electrode potential change [27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under external load, it has been generally agreed that the plastic strain will significantly reduce the corrosion resistance by directly enhancing the anodic reaction [7,11,14,16,[21][22][23][24][25][26] while the hydrogen evolution was reported to increase as well [21,22]. Despic et al [11] observed that a negative corrosion potential shifted by up to 30 times, with a marked increase in the anodic current density at the onset of the tensile plastic strain and reached an asymptotic value gradually. Plastic deformation was believed to increase the surface reactivity non-uniformly [26] and the stored energy within a material, which can be directly related to the electrode potential change [27].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused on stress corrosion cracking [6,7], corrosion fatigue [8][9][10] and hydrogen-induced cracking [11][12][13] and erosion-corrosion [14][15][16]. It has been reported that 23-33% of the low-alloy steel weight loss was attributed to the mechano-electrochemical effects, while the number could be 55-62% for austenitic stainless steels [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Par conséquent, il semble important d'identifier l'influence du comportement élasto-plastique des métaux sur les cinétiques électrochimiques liées aux processus de corrosion (adsorption, dissolution, passivation). Dans le cas particulier des processus de dissolution, quelques études de traction in-situ en milieux acides ont montré une augmentation de la densité de courant puis une diminution de celle-ci lorsque la déformation plastique augmente [9,[11][12][13][14][15]. Ce résultat important peut être interprété de multiples façons : une augmentation de l'activité de la dissolution sur les marches associées à l'émergence des lignes de glissement, une augmentation de la rugosité, une réduction des distances de diffusion en surface, une modification de l'entropie du système associée à la présence de dislocations et d'un état de contrainte, .…”
Section: Introductionunclassified
“…. [11,12]. Les tentatives d'interprétation des résultats in-situ ne distinguent que rarement les effets de la contrainte de ceux des défauts développés par la plasticité.…”
Section: Introductionunclassified